Information Security Behavior in Higher Education Institutions - Keefa Bwiino; Geoffrey Kituyi Mayoka; Lawrence Nkamwesiga; Makafui Nyamadi; Ibrahim Musenze A. (Journal of Information Security and Cybercrimes Research)
Information security remains a significant concern in higher education, evidenced by the numerous security-related incidents reported over the last decade. This study investigates the vulnerabilities and threats confronting higher education institutions and proposes information security measures to enhance safety. Key vulnerabilities identified include decentralized IT infrastructure, a diverse user base, legacy systems, insider threats, and insufficient investment in information security. Correspondingly, potential threats and attacks on information in HEIs encompass social engineering attacks, distributed denial-of-service attacks, malware, and insider breaches. Furthermore, the findings advocate for the integration of artificial intelligence in information security monitoring, the incorporation of security education into university curricula, and the implementation of multi-faceted information security measures, including technological, organizational, environmental, and human measures, to ensure robust information security protection in HEIs. The study also highlights areas for future research.